The Life in Times of Precarization: Film Interpretations of Youth Unemployment - Piepiórka, Michał (Media - Culture - Social Communication, 2019)
The goal of this paper is an analysis of film interpretations of youth unemployment. The author is particularly interested in the period after 2000 and these movies, which were focused on the involvement in precarization of the young generation, include: Krugerandy (The Krugerands, 1999) by Wojciech Nowak; Portret podwójny (A Double Portrait, 2001) by Mariusz Front; Doskonałe popołudnie (The Perfect Afternoon, 2005) by Przemysław Wojcieszek; Aleja gówniarzy (Hipster’s Avenue, 2007) by Piotr Szczepański; Ki (2011) by Leszek Dawid. The author examines the narratives about the situation on the labour market used by Polish filmmakers. Did they find the same sources of the bad situation of young generation? In what practices did they see the chances of escaping from an unfavorable situation? Did they see the labour market in a critical way? In the analysis, a term made by Guy Standing – a precariat – is used. This category did not appear in media discourse when those movies were made, so the question is if it can be useful description of the social situation of these movies.